The Use of Emoji in International Communication: A Cultural Bridge for Businesses or a Potential Pitfall - Missirian, David E (American Journal of Trade and Policy, 2021)
There is a new form of communication entering the international business world and the legal environment. It is the Emoji. It has been embraced across the globe by millennials. There are 26 million US persons entering the business community this year alone for whom the emoji is an essential communications tool. That number is matched in multiples by other countries. We must anticipate and incorporate this new mode and method of communication into our international legal structure, or we will ultimately make our legal system less effective in the global business community driving a communications wedge between our society and the rest of the world.
Keywords: commerce; emoji; communication; international business